Vocational Education Practices for Empowerment of Vulnerable Students in Lithuania and Latvia: The Pedagogical and Institutional Factors - Daukilas, Sigitas; Gedvilien, Genut; Sloka, Biruta; Buligina, Ilze; Anužis, Aivaras (Journal of Technical Education and Training, 2024)
This article aims to disclose the institutional and pedagogical factors of VET provider practices targeted to empowerment of vulnerable students for learning and employment in Lithuania and Latvia.  The research methodology and design are based on comparative study involving desk research, case studies by applying focus group interviews with representatives of the VET institutions’ teaching, support and administrative staff. Research disclosed the central role of VET teachers and other teaching staff members in empowering at-risk VET students, as well as the issue of their capacities and capacity building needs in empowering increasing volume of at-risk students in VET schools. VET schools seek to empower students by abandoning standardization and narrow specialization of skills and increased use of the individual approach in pedagogical practices. Preference is given to expanding the scope and individualization of the applied pedagogical practices for at-risk students. Increased attention is being paid to the living conditions of at-risk students outside school, addressing students' social problems, development of key skills and attitudes, coaching and methods of individual co-operation.